[Rezension von: Martirosyan, Hrach, 1964-, Iranisches Personennamenbuch, Iranian personal names in Armenian collateral tradition] - Klein, Jared S. (Journal of the American Oriental Society, 2023)
Iranisches Personennamenbuch, vol. 5, Iranische Namen in Nebenüberlieferungen Indogermanischer Sprachen, fasc. 3: Iranian Personal Names in Arme-nian Collateral Tradition. By Hrach Martirosyan. Österreichische Akademie der Wissenschaften, Phil-Hist. Kl. Sitzungsberichte, vol. 912. Vienna: Austrian Academy of Sciences Press, 2021. Pp. 453. €98 (paper); €78.40 (ebook).